Allen Varley Astin papers - Astin, Allen Varley, 1904-1984.
Correspondence, memoranda, minutes, agenda, reports, studies, congressional testimony, writings, speeches, conference papers, university teaching and training course records, research data, printed matter, and photographs documenting Astin's career at the National Bureau of Standards (1928-1969), particularly as director (1952-1969), during which time the bureau was expanded and reorganized. Topics include measurement techniques relating to electric insulating materials, telemeters, electric instrumentation, and the electrification of American industry. Astin's World War II activities at the bureau in ordnance research and the development of proximity fuzes for bombs and rockets are documented as well as his service in the London office of the U.S. Office of Scientific Research and Development as a liason with the British armed forces. Other topics include science and public policy, international cooperation among scientists, and the metric system. Includes some material relating to the career of his son, actor John Astin.
Physicist and director, National Bureau of Standards.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Astin, John; United States. -- National Bureau of Standards; United States. -- Office of Scientific Research and Development; Bombardment; Electric apparatus and appliances; Electric insulators and insulation; Electrification; Metric system; Ordnance; Proximity fuzes; Science -- International cooperation; Science and state -- United States; Telemeter; Weights and measures; World War, 1939-1945 -- Aerial operations; World War, 1939-1945 -- England -- London; Great Britain -- Armed Forces; Physicists; Public officials